PERMAINAN KARTU BILANGAN SEBAGAI ALAT PERAGA UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS V SDN 010 UJUNG BATU - Mulyasni ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the lack of motivation to learn mathematics student class VSDN 010 Ujung Batu. Goals to be achieved in this research is to improve student learningmotivation math class V SDN 010 Ujung Batu through the game card numbers as propscarried out for 1 month. This research was conducted in SDN 010 Ujung Batu. Classes thatthorough research is a class V with the number of students as many as 30 people. Thisclassroom action research was started in August 2014. This form of research is classroomaction research. The research instrument consists of instruments teacher and student activitysheets and achievement test. Based on the results of research and discussion can beconcluded that the application of the card game of numbers as props can increase studentmotivation to learn mathematics in the subject matter of integers class V SDN 010 UjungBatu, as it is seen in the first cycle of students' motivation by category reached 59.9% prettygood, and increased in the second cycle in which student learning mnotivasi be 71.3% withgood category, dnegan this shows the card game as props able to increase students'motivation in learning mathematics